A Generational Comparison of Physical and Laboratory Findings in Patients with Polyendocrine Metabolic Ovarian Syndrome in Japan - Saki Minato; Yuri Yamamoto; Hiroki Noguchi; Moeka Arata; Kou Tamura; Hidenori Aoki; Asuka Takeda; Ayana Takahashi; Tugsjargal Purevdorj; Ayaka Shinohara; Hiroaki Inui; Riyo Kinouchi; et al. (Journal of Clinical Medicine, 2026)
Background/Objectives: Women with polyendocrine metabolic ovarian syndrome (PMOS) are known to be at higher risk of developing metabolic-related disorders. Here, we conducted a retrospective observational study to compare physical and laboratory findings associated with PMOS across different generations. Methods: We analyzed 470 medical records from 155 patients with PMOS from December 2002 to March 2023. Demographic, metabolic, and hormonal data were extracted and compared among age groups: